Draft genome sequence of mycobacterium bolletii strain M24, a rapidly growing mycobacterium of contentious taxonomic status - Wong, V.L.; Chook, S.W.; Tan, J.L.; Ong, C.S.; Ng, K.P.; Ngeow, Y.F. (American Society for Microbiology, 2012)
The whole-genome sequence of Mycobacterium bolletii M24, isolated from the bronchoalveolar lavage fluid of a Malaysian patient, is reported here. The circular chromosome of 5,507,730 bp helped to clarify the taxonomic position of this organism within the M. abscessus complex and revealed the presence of proteins potentially important for pathogenicity in a human host.